2018
DOI: 10.1016/j.jjcc.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

The optimal cut-off of blood pressure related to left ventricular diastolic dysfunction and remodeling in Asian diabetic patients

Abstract: Our study showed the adverse influence of prehypertension and hypertension on subclinical LV deterioration. This finding suggested the potential clinical benefits of intensive BP control (<130/80mmHg) in patients with DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…Recent studies have reported that LV diastolic dysfunction is caused by inflammation and oxidative stress, which are known to be induced by several factors, including diabetes, hypertension, and age [16,17]. Clinical studies also reported that diabetes, hypertension, and age showed independent associations with LV diastolic dysfunction [18,19]. In the current study, age, hypertension, and some medications for hypertension were independently associated with LV diastolic dysfunction.…”
Section: Discussionsupporting
confidence: 56%
“…Recent studies have reported that LV diastolic dysfunction is caused by inflammation and oxidative stress, which are known to be induced by several factors, including diabetes, hypertension, and age [16,17]. Clinical studies also reported that diabetes, hypertension, and age showed independent associations with LV diastolic dysfunction [18,19]. In the current study, age, hypertension, and some medications for hypertension were independently associated with LV diastolic dysfunction.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies observed that systolic blood pressure was associated with an increased risk of diastolic dysfunction 17,18 . Interestingly, in our study, we found that FH+ was independent predictor of diastolic dysfunction despite lower systolic blood pressure compared to those of FH–.…”
Section: Characteristics All Subjects (N = 1011) Fh+ (N = 251) Fh− (N...supporting
confidence: 52%
“…Previous studies observed that systolic blood pressure was associated with an increased risk of diastolic dysfunction. 17 , 18 Interestingly, in our study, we found that FH+ was independent predictor of diastolic dysfunction despite lower systolic blood pressure compared to those of FH–. Based on our multivariate analysis, it seems that FH+ impact on diastolic dysfunction surpassed that of systolic blood pressure.…”
Section: Tablementioning
confidence: 45%
“…Blood pressure <120 mm of Hg systolic and <80 mm of Hg diastolic was considered as normal. 22 Blood samples were collected and all the biochemical and laboratory investigations were performed for both PCOS patients and healthy controls. Pelvic ultrasound was also done for all study groups.…”
Section: Methodsmentioning
confidence: 99%